APAKAH TRUST MEMDIASI PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE TERHADAP MINAT PENGGUNAAN QRIS? - Gunarsih, Tri; Dyah Febriyani (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The Quick Response Code Indonesian Standard (QRIS), introduced by Bank Indonesia, aims to unify digital payment systems across Indonesia. However, despite substantial growth in QRIS transactions, the national adoption target is still not achieved, especially among Generation Z, a demographic that has high digital literacy. This study investigates the influence of two Technology Acceptance Model (TAM) constructs, perceived usefulness and perceived ease of use, on intention to adopt QRIS among Gen-Z in Yogyakarta, with trust as the mediating variable. A quantitative approach was taken using purposive sampling, with data collected from 98 respondents through an online questionnaire. Data was analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings show that perceived usefulness and perceived ease of use significantly and positively influence QRIS usage intention, both directly and indirectly through trust. Trust emerges as an important mediating variable that increases the predictive power of TAM in the context of digital payment adoption. This study contributes to the theoretical advancement of TAM by integrating trust as a mediating construct, thereby enhancing its explanatory power in the context of Gen-Z digital payment adoption.